PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KEPEMIMPINAN TRANSAKSIONAL TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING PADA PT. SINAR SOSRO TANJUNG MORAWA - Corry Magdalena (Universitas Islam Negeri Sumatera Utara Medan, 2016)
Chairman of PT. Sinar Sosro Tanjung Morawa should maintain transactionalleadership and transformational leadership, since both can affect motivation andperformance of employees. The study of transformational leadership is more positiveeffect of increasing motivation and performance, but recall that effective leadership is acombination of both the leadership. This type of research is correlational study withcross sectional study approach that examines the independent variables and thedependent variables simultaneously at any given time. The population in this study wereall employees of the production of PT. Sinar Sosro Tanjung Morawa totaling 180employees, with a sampling probability sampling technique by using simple randomsampling with a total sample of 123 people. This study uses Path Analysis of Bayesianmethods, with the independent variables of transformational leadership andtransactional leadership, motivation and the dependent variable (Y1) and employeeperformance (Y2). The results of this study indicate bahwasannya the Y1 equation, thecoefficient of determination (R2) of its 11.5% influenced by variables transformationalleadership and transactional leadership. As well as in the equation Y2, the coefficient ofdetermination (R2) it is 24.3% influenced by transformational leadership, transactionalleadership and motivation. In testing of Bayesian methods obtained in the equation Y1which significantly affect motivation as an intervening variable is transformationalleadership and transactional leadership has little effect (not significant) and the equationY2 which significantly affect employees' performance is transformational leadership,transactional leadership and motivation as an intervening variable has little effect (notsignificant).Keywords: Kepemimpinan Transformasional, Kepemimpinan Transaksional, Motivasidan Kinerja Karyawan.